COMPARATIVE ASSESSMENT OF THE IMPACT OF NATURAL ANTIOXIDANTS ON THE QUALITATIVE INDICATORS OF SEMI-FINISHED PRODUCTS FROM BROILER-CHICKEN MEAT AND OXIDATIVE PROCESSES IN THEIR STORAGE - Semenov Vladimir Grigoryevich; Kuzmina Nadezhda Nikolaevna; Petrov Oleg Yuriyevich; Baimukanov Aidar Dastanbekouly; Dzhanabekova Gulmira Kumiskalievna; Sarimbekova Saule Nurgaliyevna; Nesipbayeva Aigul Kadirovna; Zhylkyshybayeva Meruert Malikovna (Scientific Journal of Pedagogy and Economics, 2019)
The effectiveness of use of dihydroquercetin bioflavonoid in comparison with other natural antioxidants was studied in the formulation of semi-finished products of broiler-chicken meat, indicating its high biological activity, positive impact on quality indicators, finished products yield and their consumer characteristics. It was established that antioxidants with various efficiency inhibit the oxidative deterioration of samples primary products used in the production of semi-finished broiler-chicken products. With the introduction of vitamin E, for 28 days of storage, the acid number was lower on average by 0.84 mg KOH/g, with the addition of vitamin C, rutin and dihydroquercetin, respectively, by 1.27; 3.52 and 3.61 mg KOH/g compared with the control sample. So, when adding tocopherol, the peroxide value in the test samples was 1.3 times lower than in the control ones. When adding ascorbic acid, rutin, and dihydroquercetin in samples of raw materials, the value of this indicator was even lower by 1.6; 1.7 and 1.9 times respectively. As a result, after 28 days of storage of test samples of poultry processing primary products, the acid number reached smaller values by an average of 29%, and the peroxide value - by 1.5–1.7 times, in reference to the control. The obtained results persuade of the high efficiency of using dihydroquercetin as an active antioxidant, making it possible to use it along with available analogues.